EXPLORING UNIVERSITY STUDENTS PERCEPTION OF STRESS AND STRESS MANAGEMENT DURING A UNIVERSITY HEALTH PROMOTION DAY - MOUSSE, FATHIA; MORRISSEY, HANA; BALL, PATRICK ANTHONY (International Journal of Current Pharmaceutical Research, 2019)
Objective: Stress, depression and anxiety are common, estimated at 19.7% people showing symptoms of these diseases. Although, effective treatment for depression and anxiety is available, they are still under diagnosed and treated to avoid stigma. The study aims to explore the impact of pharmacist-led health promotion to increase the university local population awareness about stress, the causes and management. Methods: A questionnaire-based study which included 50 participants aged 18 and over from the University of Wolverhampton. Results: The findings revealed that stress has an impact on the individuals’ lives, but they understood the effects of stress. The results informed the different factors that cause stress amongst the participants of multiple demographics. Conclusion: Change is required to improve the mental well-being of the public. This study improved the University of Wolverhampton’s student’s knowledge and awareness of mental health. It provides in-depth knowledge for a future pharmacist to learn about stress management to help patients with more advanced services given in community pharmacies. Expanding knowledge within this area could assist millions of affected people to seek help.